Complications of exercise and pharmacologic stress echocardiography - Lee, Christopher; Dow, Sam; Shah, Kajal; Henkin, Stanislav; Taub, Cynthia (Frontiers in Cardiovascular Medicine, 2023)
Stress echocardiography is a diagnostic cardiovascular exam that is commonly utilized for multiple indications, including but not limited to the assessment of obstructive coronary artery disease, valvular disease, obstructive hypertrophic cardiomyopathy, and diastolic function. Stress echocardiography can be performed via both exercise and pharmacologic modalities. Exercise stress is performed with either treadmill or bicycle-based exercise. Pharmacologic stress is performed via either dobutamine or vasodilator-mediated (i.e., dipyridamole, adenosine) stress testing. Each of these modalities is associated with a low overall prevalence of major, life-threatening adverse outcomes, though adverse events are most common with dobutamine stress echocardiography. In light of the recent COVID-19 pandemic, the risk of infectious complications to both the patient and stress personnel cannot be negated; however, when certain precautions are taken, the risk of infectious complications appears minimal. In this article, we review each of the stress echocardiographic modalities, examine major potential adverse outcomes and contraindications, assess the risks of stress testing in the setting of a global pandemic, and examine the utilization and safety of stress testing in special patient populations (i.e., language barriers, pediatric patients, pregnancy).